Safety and Efficacy of Nonanesthesiologist-Administrated Propofol during Endoscopic Submucosal Dissection of Gastric Epithelial Tumors - Keiichiro Abe; Keiichi Tominaga; Akira Kanamori; Tsunehiro Suzuki; Hitoshi Kino; Masakazu Nakano; Takeshi Sugaya; Kouhei Tsuchida; Yuichi Majima; Toshimitsu Murohisa; Makoto Iijima; Kenichi Goda; et al. (Gastroenterology Research and Practice)
Objective. There is no consensus regarding administration of propofol for performing endoscopic submucosal dissection (ESD) in patients with comorbidities. The aim of this study was to evaluate the safety and efficacy of propofol-induced sedation administered by nonanesthesiologists during ESD of gastric cancer in patients with comorbidities classified according to the American Society of Anesthesiologists (ASA) physical status. Methods. Five hundred and twenty-two patients who underwent ESD for gastric epithelial tumors under sedation by nonanesthesiologist-administrated propofol between April 2011 and October 2017 at Dokkyo Medical University Hospital were enrolled in this study. The patients were divided into 3 groups according to the ASA physical status classification. Hypotension, desaturation, and bradycardia were evaluated as the adverse events associated with propofol. The safety of sedation by nonanesthesiologist-administrated propofol was measured as the primary outcome. Results. The patients were classified according to the ASA physical status classification: 182 with no comorbidity (ASA 1), 273 with mild comorbidity (ASA 2), and 67 with severe comorbidity (ASA 3). The median age of the patients with ASA physical status of 2/3 was higher than the median age of those with ASA physical status of 1. There was no significant difference in tumor characteristics, total amount of propofol used, or ESD procedure time, among the 3 groups. Adverse events related to propofol in the 522 patients were as follows: hypotension (systolic blood pressure<90 mmHg) in 113 patients (21.6%), respiratory depression (SpO2<90%) in 265 patients (50.8%), and bradycardia (pulse rate<50 bpm) in 39 patients (7.47%). There was no significant difference in the incidences of adverse events among the 3 groups during induction, maintenance, or recovery. No severe adverse event was reported. ASA 3 patients had a significantly longer mean length of hospital stay (8 days for ASA 1, 9 days for ASA 2, and 9 days for ASA 3, P=0.003). However, the difference did not appear to be clinically significant. Conclusions. Sedation by nonanesthesiologist-administrated propofol during ESD is safe and effective, even for at-risk patients according to the ASA physical status classification.